Interfacial forces dictate the pathway of phospholipid vesicle adsorption onto silicon dioxide surfaces - Biswas, Kabir Hassan (2020)
The pathway of vesicle adsorption onto a solid support depends on the material composition of the underlying support, and there is significant interest in developing material-independent strategies to modulate the spectrum of vesicle-substrate interactions on a particular surface. Herein, using the quartz crystal microbalance-dissipation (QCM-D) technique, we systematically investigated how solution pH and membrane surface charge affect vesicle adsorption onto a silicon dioxide surface. While vesicle adsorption and spontaneous rupture to form complete supported lipid bilayer (SLBs) occurred in acidic conditions, it was discovered that a wide range of adsorption pathways occurred in alkaline conditions, including (i) vesicle adsorption and spontaneous rupture to form complete SLBs, (ii) vesicle adsorption and spontaneous rupture to form incomplete SLBs, (iii) irreversible adsorption of intact vesicles, (iv) reversible adsorption of intact vesicles, and (v) negligible adsorption. In general, SLB formation became more favorable with increasingly positive membrane surface charge although there were certain conditions at which attractive electrostatic forces were insufficient to promote vesicle rupture. To rationalize these findings, we discuss how solution pH and membrane surface charge affect interfacial forces involved in vesicle-substrate interactions. Taken together, our findings present a comprehensive picture of how interfacial forces dictate the pathway of phospholipid vesicle adsorption onto silicon dioxide surfaces and offer a broadly applicable framework to characterize the interactions between phospholipid vesicles and inorganic material surfaces.